2019
DOI: 10.1021/acsbiomaterials.9b00070
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Assessment of Intervertebral Disc Degeneration via a Collagen Hybridizing Peptide

Abstract: During aging, wear, and tear of intervertebral discs, human discs undergo a series of morphological and biochemical changes. Degradation of extracellular matrix proteins, e.g., collagen, arises as an important contributor and accelerator in this process. Existing methods to detect collagen degradation at the tissue level include histology and immunohistochemistry. Unfortunately, most of these methods only depict overall collagen content without the ability to specifically discern degraded collagen and to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…However, the SHG intensity within the AF was generally decreased in 12 months old WT and Phlpp1 KO mice. A recent study by Xiao et al 49 demonstrated a strong correlation between AF collagen damage and age by using a collagen-hybridizing peptide (which integrates into damaged collagen) and observed a significant increase in damaged collagen between 6–8 months and 10–12 months old mice. Given that the damage to the secondary and tertiary protein structure of collagen is also detectable by decreased SHG intensity 50 , their findings supported the lower SHG intensity detected in the AF tissues of 12 months old mice relative to 6 months group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the SHG intensity within the AF was generally decreased in 12 months old WT and Phlpp1 KO mice. A recent study by Xiao et al 49 demonstrated a strong correlation between AF collagen damage and age by using a collagen-hybridizing peptide (which integrates into damaged collagen) and observed a significant increase in damaged collagen between 6–8 months and 10–12 months old mice. Given that the damage to the secondary and tertiary protein structure of collagen is also detectable by decreased SHG intensity 50 , their findings supported the lower SHG intensity detected in the AF tissues of 12 months old mice relative to 6 months group.…”
Section: Discussionmentioning
confidence: 99%
“…Besides Akt, Phlpp1 also directly controls other cell survival signaling pathways, including PKC and p70 S6 kinase 15,52,53 and the pro-apoptotic kinase Mst1 54,55 , which likely explains the protective effect of Phlpp1 depletion on cell proliferation but less pronounced effects on Akt phosphorylation. Phlpp1 deficiency also activates the negative feedback regulation of the Akt pathway, where PTEN, a lipid phosphatase, participates in the feedback loop by dephosphorylating PI3K to balance the level of phosphorylated Akt 29,49 . PTEN is an another phosphatase that has several off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…Since the number of defects increases with degeneration, we note severely degenerated IVDs would have an increase in structural disruptions in addition to the collagen network changes described in this SHG study. The fibrosis hypothesis presented suggests that the original collagenous structure within the AF degenerates and is replaced with new collagen, and future studies can assess degenerated collagen using collagen hybridizing peptide as a probe 54‐56 . Lastly, future SHG analysis concurrent with biomechanical experiments may further elucidate structure‐function relationships since structural changes in collagen are expected upon load application 49,57‐59 …”
Section: Discussionmentioning
confidence: 98%
“…The fibrosis hypothesis presented suggests that the original collagenous structure within the AF degenerates and is replaced with new collagen, and future studies can assess degenerated collagen using collagen hybridizing peptide as a probe. [54][55][56] Lastly, future SHG analysis concurrent with biomechanical experiments may further elucidate structurefunction relationships since structural changes in collagen are expected upon load application. 49,[57][58][59] In conclusion, this study applied SHG imaging and multiple image processing algorithms to quantify the spatial changes in collagen structure with IVD degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence microscopy of rat skin tissue slide (without mounting) was performed using a Nikon DS‐Ri2 digital microscope camera mounted on a Nikon Eclipse E‐600 microscope with a TRITC channel. Images were captured with the exact same exposure time and analog gain at 200× magnification using the NIS Elements Software (Nikon Corp.) following the published protocols …”
Section: Methodsmentioning
confidence: 99%